Tom Clancy Flash point [large type] - Bentley, Don; Clancy, Tom, 1947-2013 (Clancy, Tom, 1947-2013. Jack Ryan Jr. novel, 2023)
"When a benign surveillance operation takes a deadly turn, Jack Ryan Jr. finds himself locked in a struggle with an unseen enemy bent on destroying the Campus. The chase leads Jack to the South China Sea where a midair collision between aircraft from rival nations threatens to serve as a flash point for the entire region. As tensions escalate, Jack's mysterious adversary executes a brilliant campaign to paralyze the American government. With the odds stacked against him, Jack and his team must stop the world's two remaining super powers from stumbling into war even as the noose around the Campus grows ever tighter"--